Sulfonated Nanomaterials with Broad-Spectrum Antiviral Activity Extending beyond Heparan Sulfate-Dependent Viruses - Cagno, Valeria (Antimicrob Agents Chemother, 2020)
Viral infections are among the main causes of death worldwide, and we lack antivirals for the majority of viruses. Heparin-like sulfated or sulfonated compounds have been known for decades for their ability to prevent infection by heparan sulfate proteoglycan (HSPG)-dependent viruses but only in a reversible way. We have previously shown that gold nanoparticles and β-cyclodextrins coated with mercapto-undecane sulfonic acid (MUS) inhibit HSPG-dependent viruses irreversibly while retaining the low-toxicity profile of most heparin-like compounds. In this work, we show that, in stark contrast to heparin, these compounds also inhibit different strains of influenza virus and vesicular stomatitis virus (VSV), which do not bind HSPG. The antiviral action is virucidal and irreversible for influenza A virus (H1N1), while for VSV, there is a reversible inhibition of viral attachment to the cell. These results further broaden the spectrum of activity of MUS-coated gold nanoparticles and β-cyclodextrins.